An improved dosage regimen of sertraline hydrochloride in the treatment for premature ejaculation: an 8‐week, single‐blind, randomized controlled study followed by a 4‐week, open‐label extension study. (9th December 2013) - Xu, G.; Jiang, H.‐W.; Fang, J.; Wen, H.; Gu, B.; Liu, J.; Zhang, L.‐M.; Ding, Q.; Zhang, Y.‐F.
Summary What is known and objective This study aimed at evaluating the safety and efficacy of an improved dosage regimen of sertraline in patients with premature ejaculation (PE) and to examine whether the premature ejaculation diagnostic tool (PEDT) can be used as a measure of treatment response in these patients. Methods A total of 218 PE patients were randomized into control (n = 61) and treatment (n = 157) groups to receive mycelium of cordyceps sinensis C4 and sertraline 50 mg daily for 8 weeks, respectively. Following this blinded stage, sixty‐three patients chose to take sertraline 100 mg daily for an additional 4‐week period, and 80 other patients continued treatment with sertraline 50 mg. Main outcome measures include intravaginal ejaculatory latency time (IELT), PEDT score and Clinical Global Impression of Change (CGIC) score. Results At weeks 4 and 8, mean IELT of patients who subsequently chose to take 100 mg of sertraline was significantly lower than that of patients who continued taking 50 mg of sertraline, although the IELT value was comparable between the two groups of patients at baseline. However, with an additional 4‐week treatment, the mean IELT increased significantly more in the 100‐mg group than in the 50‐mg continuation group. Similar results were also obtained in the analyses of the PEDT and CGIC scores. Both regimens were well tolerated, and relapse rate did not differ significantly between the two groups. What is new and conclusion These findings suggest that PE patients not responding to an 8‐week treatment with sertraline 50 mg can benefit from an additional 4‐week treatment with sertraline 100 mg and that the PEDT may be a valid measure of treatment response in PE patients.